A medicina de Nina Rodrigues: análise de uma trajetória científica Brazilian physician Nina Rodrigues: analysis of a scientific career - Marcos C. Maio (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1995)
Uma das maneiras mais profícuas de se pesquisar a história da medicina brasileira na passagem do século XIX para o XX é a investigação da trajetória profissional de determinados médicos que tiveram posições de relevo no processo de mudanças que atingiu o campo médico à época. Neste sentido, este artigo tem por objetivo analisar a carreira acadêmico-profissional de Raimundo Nina Rodrigues, a partir da noção de campo científico de Pierre Bourdieu. Partindo do princípio de que o campo médico é um espaço de confrontos estruturalmente determinado pelos embates passados, onde os médicos buscam monopolizar a autoridade/competência científica, considero que o perfil médico de Nina Rodrigues é um indicador preciso do processo de especialização e concorrência que se desenvolveu naquele momento. One of the most productive ways of investigating the history of Brazilian medical practice at the turn of this century is to focus on the fruitful and ambiguous careers of those physicians that played an important role in the changes affecting the medical field at that time. This paper aims at analyzing the scientific career of physician-anthropologist Raimundo Nina Rodrigues, taking as its conceptual basis Pierrre Bourdieu's notion of "scientific field ". The paper's point of departure is the notion that the medical field is a space of confrontation that is structurally determined by previous conflicts in which physicians try to monopolize claims to scientific authority and competence. Nina Rodrigues' medical profile appears in this context as a precise indicator of the process of specialization and competition that took place during that period.